Burden of Reproductive Organ Cancer of Females in the Population-based Cancer Registry in Nepal - Baral, Gehanath; Marahatta, Sujanbabu; Singh, Sumer (Journal of Nepal Health Research Council, 2024)
Background: There are sporadic facility-based reports but an information gap in the cancer burden in the community is apparent. To address this, the Nepal Health Research Council (NHRC) started a Population-based Cancer Registry (PBCR) in 2018 in the country. Thus, this study aims to identify the cancer burden in the female population, especially in the reproductive organs. Methods: A quantitative database analysis of the Population-based Cancer Registry for year 2018 and 2019 was performed. Data entered in the TSV (Tab-separated values) files were imported to MS Excel and SPSS data Window and variables regrouped before analysis. The national census, WHO standardized population, and registry data were used for the descriptive analysis of the registry variables. Ethical approval was taken from the Ethical Review Board of NHRC. Result: Out of 6854 cancer registries, the female population was 3590 with a male-to-female ratio of 10:11. This registry covers 10.75% of the country’s population. The crude and age-standardized cancer incidence rates were 1.24% and 66.2 per 100,000 for the female population respectively. Reproductive organs (21%) and breast (19.7%) cancers are the most common in females, and out of reproductive organs cervical (58%) and ovarian (25%) cancers are the commonest. Surgery was the main treatment modality (32.7%) with or without chemotherapy and radiotherapy. Conclusions: The burden of cancer is higher in females because of breast cancer. Reproductive organ cancers and breast cancers share an equal burden of around 20% each. The most common female genital cancer is of uterine cervix followed by the ovary. Keywords: Breast; burden of cancer; cancer registry; cervix; ovary.